“No hands, no chocolate”: Gender, race, disability and class in the film Intouchables - Björnsdóttir, Kristín; L’orange, Kristín Stella (Menntavísindasvið Háskóla Íslands, 2015)
Background: The interplay of culture and disability is an interesting topic to explore, and by focusing on different cultural productions it is possible to understand societies’ values at different times in history. Films can be categorized as cultural productions that express values in time and space, and can potentially influence public opinion. This article is about the French film Intouchables, which premiered in 2011 and was well received and nominated for several awards. The film is based on a true story about a Parisian aristocrat, Philippe, who is a quadriplegic millionaire, and Driss, his personal assistant, an immigrant from Senegal who has no formal training or knowledge of how disabled people should be assisted and supported in their daily lives. The film was directed by Oliver Nakache and Éric Toledano, and although the film was very popular in Europe, including Iceland, it received mixed reviews from film critics. It was critiqued for underestimating the seriousness of living with quadriplegia and for being borderline racist (O‘Sullivan, 2012). However, disability is a common theme in film and TV, and in fact the disability studies scholar Tobin Sieber (2008) claims that there is a strong link between playing the role of a disabled character and receiving Oscar nominations. Common representations of disability in film and media are characters who are violent, dependent on others or incompetent, and it is possible that audiences transfer these ideas to disabled people living in their community (Saffran, 2000). Films and media commonly use disability stereotypes portraying disabled people in negative ways, and similar practices can be found in relation to other minority groups. Tolenado and Nakache (2012) announced publicly that their main goal was to make a feel-good, buddy film, but they also wanted to stay true to the original story. Since the film became so widely popular in Iceland, and since disability in film has received little attention in the Icelandic research literature, this film is an ...